Professional practice environment and burnout among nurses - Renata Cristina Gasparino; Edinêis de Brito Guirardello (Rev Rene)
Objective: to evaluate the professional practice environment of nurses, their relationship with burnout syndrome and the differences among three institutions. Methods: a cross-sectional study developed at one secondary and two tertiary hospitals, with 278 nurses, who filled the Nursing Work Index Revised – Brazilian Version and the Maslach Burnout Inventory. Results: most of these nurses showed job satisfaction and good quality of health care, while few informed intentions to leave their jobs. When comparing the institutions, the secondary level one had more autonomy in nursing practice, more control over the work environment, better relationship with physicians, and lower levels of emotional exhaustion. Conclusion: these findings contribute for the implementation of changes to improve the nursing professional practice, enabling to achieve the satisfaction of those involved in the process, such as patients, professionals, and institutions.